Singlet oxygen-based electrosensing by molecular photosensitizers - Trashin, Stanislav (Nat Commun, 2017)
Enzyme-based electrochemical biosensors are an inspiration for the development of (bio)analytical techniques. However, the instability and reproducibility of the reactivity of enzymes, combined with the need for chemical reagents for sensing remain challenges for the construction of useful devices. Here we present a sensing strategy inspired by the advantages of enzymes and photoelectrochemical sensing, namely the integration of aerobic photocatalysis and electrochemical analysis. The photosensitizer, a bioinspired perfluorinated Zn phthalocyanine, generates singlet-oxygen from air under visible light illumination and oxidizes analytes, yielding electrochemically-detectable products while resisting the oxidizing species it produces. Compared with enzymatic detection methods, the proposed strategy uses air instead of internally added reactive reagents, features intrinsic baseline correction via on/off light switching and shows C-F bonds-type enhanced stability. It also affords selectivity imparted by the catalytic process and nano-level detection, such as 20 nM amoxicillin in μl sample volumes.